Curve-passing Performance of New Generation Single-axle Straddle Monorail Vehicle - Guomin LYU; Bailing YANG; Zixue DU; Xujie YANG; Zhenzhen YE; Long RAN (Chengshi guidao jiaotong yanjiu, 2024)
[Objective] The curve-passing performance of a new-model single-axle straddle monorail vehicle on small-radius non-linear curve tracks and linear curve tracks is researched and analyzed. [Method] A dynamics simulation analysis model is established using multi-body dynamics software. Suitable evaluation indicators are selected based on the vehicle structural characteristics. The minimum curve radius is determined using a method of combining statics and dynamics. Through dynamics simulation, various vehicle dynamics performance parameters such as monorail vehicle tire stress condition, running wheel flange angle, and overturning coefficient are calculated for different working conditions. The stress situation of the vehicle is obtained for both small-radius non-linear curve segments and linear segments with different curve radii. [Result & Conclusion] The new generation single-axle monorail vehicle demonstrates excellent curve-passing performance on small radius non-linear curve tracks and linear tracks with various curve radii.